Increased focal internal carotid artery angulation in patients with posterior communicating artery aneurysms. (23rd May 2020) - Rosato, Richard; Comptdaer, Gabriela; Mulligan, Ryan; Breton, Jeffrey M; Lesha, Emal; Lauric, Alexandra; Malek, Adel M
Abstract : Background: Aneurysms at the posterior communicating artery (PCOM) origin represent the most common location on the internal carotid artery (ICA), and are associated with greater recurrence following endovascular treatment. We evaluate the association between ICA angulation in three-dimensional (3D) space and PCOM aneurysmal development, using high-resolution 3D rotational angiography (3DRA) studies. Methods: 3DRA datasets were evaluated in 70 patients with PCOM aneurysms, 31 non-aneurysmal contralateral, and 86 healthy controls (187 total). The local angle formed by upstream and downstream ICA segments at the PCOM origin, αICA@PCOM, was measured using 3DRA multiplanar reconstruction. Computational fluid dynamics (CFD) analysis was performed on parametric and patient-based models. Results: αICA@PCOM was significantly larger in aneurysm-bearing ICA segments (68.14±11.91°) compared with non-aneurysmal contralateral (57.17±10.76°, p<0.001) and healthy controls (48.13±13.68°, p<0.001). A discriminant threshold αICA@PCOM value of 61° (87% specificity, 80% sensitivity) was established (area under the curve (AUC)=0.88). Ruptured PCOM aneurysms had a significantly larger αICA@PCOM compared to unruptured (72.65±15.16° vs 66.35±9.94°, p=0.04). In parametric and patient-based CFD analysis, a large αICA@PCOM induces high focal pressure at the PCOM origin, relatively low wall shear stress (WSS), and high proximal WSS spatial gradients (WSSG). Conclusion: ICA angulation at PCOM origin is significantly higher in vessels harboring PCOM aneurysms compared with contralateral and healthy ICAs. This sharper bend in the ICA leads to high focal pressure at the aneurysm neck, low focal WSS and high proximal WSSG. These findings underline the importance of morphological ICA variations and the likelihood of PCOM aneurysm, an association which can inform clinical decisions and may serve in predictive analytics.